"Cognitive Journalism": The Modernizing of Journalism and Issues of Knowledge Industry in The Media - AlQahtani, Saud Rubaya Mousa (Journal of Humanities & Social Sciences, 2024)
The media play an important and influential role in obtaining news and information, creating knowledge, and spreading public awareness, despite the difficult conditions it is experiencing, including the decline of their economies and traditional business models, and the deterioration in their position as sources of knowledge and news, with the rise of digital media use. This article aims to shed light on the role of journalism in the knowledge industry, in light of the wide-ranging transformation witnessed by the media environment, and the claims that digital media and artificial intelligence technology will soon replace it, as a tool for transferring and expanding knowledge. It also reveals the most prominent challenges and issues facing media markets in the knowledge industry, including the current of information chaos, audience involvement in content production, selective exposure to news, and the widening knowledge and digital gap. It also outlines the features for developing the knowledge industry in the media and the modernizing of professional journalistic practices in the digital age and its transformation into knowledge-based journalism. This article argues that Cognitive journalism may have excited divisions within newsrooms, and its increasing dissonance in the production and control of content, which renews assumptions about the extent to which people have the right to own, use, and dissemination information.
Keywords: Digital Gap; Epistemology; knowledge Economy; Digital Media; Media Effect; Journalism Crisis